Attention‐deficit hyperactivity disorder (ADHD): an updated review of the essential facts. Issue 6 (14th April 2014) - Tarver, J.; Daley, D.; Sayal, K.
Abstract Attention‐deficit hyperactivity disorder (ADHD) is a complex disorder that can affect individuals across the lifespan. It is associated with substantial heterogeneity in terms of aetiology, clinical presentation and treatment outcome and is the subject of extensive research. Because of this, it can be difficult for clinicians to stay up to date with the most relevant findings and know how best to respond to parents' questions and concerns about the disorder and interventions. This is a narrative review that aims to summarize key findings from recent research into ADHD and its treatment that clinicians can share with families in order to increase their knowledge about ADHD and intervention options. ADHD develops as a result of complex interplay between interdependent genetic and non‐genetic factors. The disorder is associated with substantial impairments in functioning and poor long‐term outcomes. Pharmacological and non‐pharmacological treatment options are available for symptom management and to improve function, but functioning outcomes often fail to normalize in children with ADHD. Despite extensive advances in understanding this complex disorder, it is clear that there is still a long way to go. In particular, we address the need for future non‐pharmacological interventions to be more specifically targeted for ADHD symptoms and its commonly associated functioning deficits in order to ensure the best long‐term outcomes for children with ADHD.